An experimental study on stress concentration factors of stainless steel hybrid tubular K-joints. (December 2020) - Feng, Ran; Tang, Chi; Roy, Krishanu; Chen, Zhenming; Chen, Boshan; Lim, James B.P.
Abstract: This paper describes a test program on the stress concentration factors (SCFs) of stainless steel hybrid tubular (SSHT) joints with square hollow section (SHS) braces and circular hollow section (CHS) chord and SSHT joints with CHS braces and SHS chord. The load was applied to the brace for all test specimens. Twenty specimens in total, including ten overlapped and ten gapped tubular K-joints, were tested. Different geometric parameters were used which include brace width-to-chord diameter ratio ( β 1  =  b 1 / d 0 ), brace-to-chord thickness ratio ( τ 1  =  t 1 / t 0 ) and chord diameter-to-thickness ratio (2 γ 1  =  d 0 / t 0 ) for SHS-to-CHS hybrid tubular joints, brace diameter-to-chord width ratio ( β 2  =  d 1 / b 0 ), brace-to-chord thickness ratio ( τ 2  =  t 1 / t 0 ) and chord width-to-thickness ratio (2 γ 2  =  b 0 / t 0 ) for CHS-to-SHS hybrid tubular joints. A number of strain gauges were used at the hot spot locations for various tubular joints. The hot spot stress (HSS) method was used to determine the SCFs of SSHT joints using the quadratic extrapolation method. This was a consequence of the stress distributions around the intersection area of SHS-to-CHS and CHS-to-SHS hybrid tubular joints being nonlinear. Results found the maximum SCFs for hybrid overlapped tubular K-joints with square braces and circular chord to be located at the hot spot location at an angle of 135° between the SHS brace and the CHS chord. This is characterized as line A. The maximum SCFs of hybrid gapped tubular K-joints with square braces and circular chord were located at the hot spot location at an angle of 45° between the SHS tension brace and the CHS chord (characterized as line C) and at an angle of 45° between the SHS compression brace and the CHS chord (characterized as line E). The maximum SCFs of hybrid overlapped tubular K-joints with circular braces and square chord were located at the hot spot location at an angle of 180° to the CHS brace. The maximum SCFs of hybrid gapped tubular K-joints with circular braces and square chord were located generally at the hot spot location at an angle of 0° to the CHS brace. Test results were compared against the design predictions in accordance with the current design guidelines of the International Committee for the Development and Study of Tubular Structures (CIDECT, 2001). Upon comparison, it was found that the design formulas of CIDECT (2001) overestimate the maximum SCFs of SHS-to-CHS hybrid gapped tubular K-joints. For the CHS chord and SHS braces of hybrid overlapped tubular K-joints, the design formulas overestimate the maximum SCFs for most of the specimens. Furthermore, for the SHS chord and CHS braces of hybrid gapped tubular K-joints, the design formulas of CIDECT (2001) overestimate the maximum SCFs. For the SHS chord and CHS braces of hybrid overlapped tubular K-joints, the CIDECT (2001) design formulas were unconservative when determining the maximum SCFs of such joints. Highlights: ● Tests were conducted on SCFs of stainless steel SHS-to-CHS and CHS-to-SHS hybrid tubular K-joints. ● The maximum SCFs of hybrid overlapped and gapped tubular K-joints were located at various hot spot locations. ● Design formulas of CIDECT overestimate the maximum SCFs of SHS-to-CHS hybrid overlapped and gapped tubular K-joints. ● Design formulas of CIDECT overestimate the maximum SCFs of CHS-to-SHS hybrid gapped tubular K-joints. ● Design formulas of CIDECT are unconservative for the maximum SCFs of CHS-to-SHS hybrid overlapped tubular K-joints.